Typology of a Tetraconch in the Russian Baroque Church Architecture - Yakovlev, Alexey N. (Actual Problems of Theory and History of Art, 2020)
Tetraconch temples occupy a significant place in the church architecture of Russia of the 18th century. This architectural type, associated with the influence of Ukraine, originated in the period of the Naryshkin style, actively developed in the Baroque era, and then gradually died out in the era of classicism.The relevance of the research lies in the fact that three regional lines of development of the tetraconch type in the architecture of the Russian Baroque were revealed: Ukrainizing, Moscow, and St. Petersburg. The first is connected with the traditional architecture of Ukraine of the 17th century, the second was repelled by the Naryshkin style monuments, and the third was based on the image of St. Peter’s Cathedral in the Vatican. In Moscow monuments, the central core was above the cruciform apses of the tetraconch, while in the Ukrainian churches the apses were of equal height with the central cell. The churches of Petersburg had a complicated plan in the form of a quadrifolia and five domes located in the center and at the corners. It is important to note that these three lines, however, were not isolated from each other. They actively influenced one another, not only going beyond the framework of their region, but also generating complex hybrid variants of architectural compositions.